1995
DOI: 10.1007/bf02310326
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional shunt flow across a ventricular septal defect: Pulsed doppler echocardiographic analysis

Abstract: Pulsed Doppler echocardiographic and hemodynamic examinations were performed in 31 patients (mean age 17.8 years) with isolated ventricular septal defect (VSD). Three groups were studied: group I (n = 6) patients had severe pulmonary vascular obstructive disease (PVOD); group II (n = 12) patients had pulmonary hypertension (PH) without severe PVOD; group III (n = 13) patients had no PH. Bidirectional shunting was detected in 9 VSD patients (6 in group I and 3 in group II). Patients with low to moderately eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Another controversial decision was the timing of closing the VSD in this case. We decided to close the VSD in that early stage because, according to the report of Stojnic and colleagues, 1 the shunt flow pattern across the VSD in patients with Eisenmenger syndrome is a combination of a left-to-right shunt in the early systolic period and a right-to-left shunt in the late systolic to diastolic period, with an overall Qp/Qs equal to 1 (1.1 Ϯ 0.4 in that study) and a blood mixing percentage of approximately 24%. Therefore the closure of VSD, in theory, decreases the mixing of deoxygenated and oxygenated blood but does not increase the workload of the right ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…Another controversial decision was the timing of closing the VSD in this case. We decided to close the VSD in that early stage because, according to the report of Stojnic and colleagues, 1 the shunt flow pattern across the VSD in patients with Eisenmenger syndrome is a combination of a left-to-right shunt in the early systolic period and a right-to-left shunt in the late systolic to diastolic period, with an overall Qp/Qs equal to 1 (1.1 Ϯ 0.4 in that study) and a blood mixing percentage of approximately 24%. Therefore the closure of VSD, in theory, decreases the mixing of deoxygenated and oxygenated blood but does not increase the workload of the right ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that to-and-fro or R-L shunt in diastole was documented in some patients with VSD, who had large VSD or were accompanied by severe pulmonary hypertension. 4,5 The finding of continuous R-L shunt across morphologically small VSD without advanced pulmonary hypertension might be unique to patients with LVAD.…”
Section: )mentioning
confidence: 99%
“…[2][3][4] Various Doppler methods have been used and validated to access haemodynamics of VSDs. These includepulmonary to systemic flow ratio (Qp: Qs) method, 5 time interval from Q wave to onset of shunt method, 6 proximal isovelocity surface area (PISA) method, 7,8 and 3D echocardiography. 9,10 However, in case of bi-directional flow across VSD, only few studies describe Doppler assessment.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, in case of bi-directional flow across VSD, only few studies describe Doppler assessment. 6,11…”
Section: Introductionmentioning
confidence: 99%